Роль інноваційної діяльності у практичній підготовці майбутніх учителів початкової школи - Орос Ільдіко; Oros Ildiko; Orosz Ildikó; Біда Олена; Bida Olena; Гуттерер Єва; Hutterer Éva (Видавництво «Код», 2025)
Резюме. Педагогічна практика є цілісним процесом, невіддільним від теоретичного складника. Вона буде ефективною за умови сформованості складників професійної компетентності: інтегральної, загальних та фахових. Використання можливостей педагогічної практики для набуття досвіду реалізації інтегрованого навчання студентів є важливим, оскільки під час педагогічної практики відбувається відпрацювання, закріплення та збагачення теоретичних знань, а також розвиток і зміцнення практичних умінь і навичок майбутніх учителів. Практична готовність характеризується сформованістю у студентів умінь, що розкриті у статті. Необхідною особливістю успішності освіти є використання інноваційних методів навчання, включення до навчально-виховного процесу новітніх наукових знань, застосування стандартів якості освіти світового рівня.

Abstract. One of the priority tasks of pedagogical education is to determine the components of professional competence and clearly formulate them in educational and professional programs of specialties. Pedagogical practice is a holistic process, inseparable from the theoretical component.It will be effective provided that the components of professional competence are formed: integral, general, and specialized. Using the opportunities of pedagogical practice to gain experience in implementing integrated student learning is important, since during pedagogical practice, theoretical knowledge is practiced, consolidated, and enriched, as well as the development and strengthening of practical skills and abilities of future teachers. In the process of innovative activity, a primary school teacher has to solve problems related to the age and individual characteristics of a younger student. This is reflected in the nature and content of innovations in primary school. Practical readiness is characterized by the formation of the following skills in students: to prepare and conduct creative lessons with elements of innovation on a given topic; to independently evaluate the results of their activities; to work with various sources; to plan and conduct various extracurricular activities, to use active methods of teaching and education; conduct scientific and methodological work, use research and experimental forms of pedagogical activity and the experience of teachers; organize individual work with students and their parents, etc. In this regard, a necessary feature of successful education is the use of innovative teaching methods, the inclusion of the latest scientific knowledge in the educational process, and the application of world-class education quality standards. The effective formation of future teachers’ readiness for innovative activity is facilitated by a specially developed system of creative learning situations and the identification of the main components of creative innovative activity. One of the directions of education at the current stage of development is its informatization, therefore it is important to conduct targeted work on the implementation and application of information and communication technologies in the educational process.
The role of innovative activities in the practical training of future primary school teachers
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-16?authuser=0
Keywords: інноваційна діяльність; педагогічна практика; практична підготовка; майбутні учителі початкової школи; інноваційна діяльність; творчість